What linear estimators miss: Re-examining the effects of family income on child outcomes - Katrine V. Løken; Magne Mogstad; Matthew Wiswall (Institute for the Study of Labor (IZA), 2010)
This paper uses a rich Norwegian dataset to re-examine the causal relationship between family income and child outcomes. Motivated by theoretical predictions and OLS results that suggest a nonlinear relationship, we depart from previous studies in allowing the marginal effects on children's outcomes of an increase in family income to vary across the income distribution. Our nonlinear IV and fixed-effect estimates show an increasing, concave relationship between family income and children's educational attainment and IQ. The linear estimates, however, suggest small, if any, effect of family income, because they assign little weight to the large marginal effects at the lower part of the income distribution.
Keywords: J13; C21; C23; 330; Family income; child development; nonlinearities; fixed effects estimation; instrumental variables estimation; linear models; Kinder; Bildungsniveau; Haushaltseinkommen; Schätzung; Nichtlineares Verfahren; Norwegen